Measuring students’ creative thinking skills with SCI-Fi (Science Creative Instrument in Fluids): How Suitable Is It? - Nur Endah Susilowati; Irwandani Irwandani; Fitria Arifiyanti; M. Reza Dwi Saputra; Nuzulira Janeusse Fratiwi (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
This study aims to develop SCI-Fi (Science Creative Instrument in Fluids), an essay-based tool designed to accurately assess students’ creative thinking skills in physics by encouraging imagination and originality in problem-solving. The research adopts a Research and Development (R&D) approach based on the ADDIE model. To evaluate its quality, item validation was conducted using the Rasch model with 95 student respondents. The results show that SCI-Fi is valid and reliable, making it suitable for measuring creative thinking in physics. Additionally, it serves as a valuable tool for educators to identify students’ creative thinking profiles and plan targeted interventions, as well as for curriculum developers and researchers to promote creativity in physics education.